PENGARUH LIKUIDITAS, KAPASITAS OPERASI, DAN UKURAN PERUSAHAAN TERHADAP FINANCIAL DISTRESS PADA PERUSAHAAN TEKSTIL YANG TERDAFTAR DI BURSA EFEK INDONESIA - Wahyuni , Dewi Suci; Damayanti, Damayanti (JURNAL EKONOMI, 2022)
This study aims to prove the effect of liquidity, operating capacity and firm size on the prediction of financial distress of textile companies listed on the IDX for the 2016-2020 period. The population used in this study are textile companies listed on the Indonesia Stock Exchange for the 2016-2020 period. The population of the company is 43, while the sample used is 18 samples of textile companies listed on the BEI. There were 58 observations (63.7%) who did not experience financial distress and there were 32 observations (35.2%) who experienced financial distress. The sample selection technique used purposive sampling. The data analysis technique used logistic regression analysis. The results of this study indicate that Liquidity (CR) has an insignificant negative effect on financial distress, Operating Capacity (TAT) has an insignificant negative effect on financial distress. While company size has a positive and insignificant effect (LN) Cox Snell's R Square value is 0.133 and Negelkerke's R Square value is 0.183 as the variability of the dependent variable, namely financial distress can be explained by independent variables which include liquidity (CR), operating capacity (TAT), size company (LN) 18.3% while 81.7% is explained by variations of other variables that are not explained in this study.